Early response evaluation using CT-perfusion one day after transarterial chemoembolization for HCC predicts treatment response and long-term disease control. Issue 90 (May 2017) - Tamandl, Dietmar; Waneck, Fredrik; Sieghart, Wolfgang; Unterhumer, Sylvia; Kölblinger, Claus; Baltzer, Pascal; Ba-Ssalamah, Ahmed; Loewe, Christian
Highlights: CT perfusion can predict response to TACE within one day after treatment. This response is sustained during long-term follow up. Treatment related decisions, e.g. retreatment, can now be made within one day of therapy. Abstract: Purpose: To determine the value of CT perfusion (CTP) for early response assessment after transarterial chemoembolization (TACE) for hepatocellular carcinoma (HCC). Materials and methods: Between April 2013 and April 2015, 41 HCC (16 patients) were included in this study. CT perfusion was performed before and one day after TACE. Blood flow (BF), blood volume (BV), time to start (TTS), arterial liver perfusion (ALP), portal liver perfusion (PVP) and hepatic perfusion index (HPI) were measured. Quantitative perfusion values before and after TACE were compared to the response assessed using mRECIST criteria six weeks after TACE and long-term outcome was assessed. Results: Twenty-one lesions (51%) had complete remission (CR) and five (12%) had partial response (PR) six weeks after TACE. CTP parameters were significantly reduced after TACE in responders (PR, CR, p < 0.001) while no difference was observed in non-responders. ALPpost was superior in the prediction of CR compared to BFpost and BVpost (p < 0.001) with a sensitivity, specificity, PPV, NPV, and accuracy of 90%, 90%, 91%, 90%, and 91%, respectively. Only 3/21 lesions with CR recurred, with a mean local-recurrence-free survival of 19.6 months. Conclusion: CT perfusion detects lesions with complete response one day after TACE, and is a feasible tool for early response assessment.